India : Financial Sector Assessment Program-Detailed Assessments Report on Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses the findings of the assessments on Basel Core Principles for Effective Banking Supervision in India. The Reserve Bank of India is to be commended for its tightly controlled regulatory and supervisory regime, consisting of higher than minimum capital requirements; frequent, hands-on, and comprehensive onsite inspections; and a conservative liquidity risk policy and restrictions on banks' capacity to take on more volatile exposures. Despite this strong performance, several gaps and constraints in the implementation of the regulatory and supervision framework remain. The most significant gaps are in the area of international and, to a lesser extent, domestic supervisory information sharing and cooperation.